Image Denoising Based on Improved Wavelet Threshold Function for Wireless Camera Networks and Transmissions. (30th September 2015) - Wang, Xiaoyu; Ou, Xiaoxu; Chen, Bo-Wei; Kim, Mucheol
Abstract : A new wavelet threshold denoising function and an improved threshold are proposed. It not only retains the advantages of hard and soft denoising functions but also overcomes the disadvantages of the continuity problem of hard denoising function and the constant deviation of the soft denoising function in the new method. In the case of the improved threshold conditions, the new threshold function has a better performance in outstanding image details. It can adapt to different images by joining an adjusting factor. Simulation results show that the new threshold function has a better ability of performing image details and a higher peak signal to noise ratio (PSNR).